2019
DOI: 10.1002/anie.201913309
|View full text |Cite
|
Sign up to set email alerts
|

Single Chromium Atoms Supported on Titanium Dioxide Nanoparticles for Synergic Catalytic Methane Conversion under Mild Conditions

Abstract: Direct conversion of methane to value‐added chemicals with high selectivity under mild conditions remains a great challenge in catalysis. Now, single chromium atoms supported on titanium dioxide nanoparticles are reported as an efficient heterogeneous catalyst for direct methane oxidation to C1 oxygenated products with H2O2 as oxidant under mild conditions. The highest yield for C1 oxygenated products can be reached as 57.9 mol molCr−1 with selectivity of around 93 % at 50 °C for 20 h, which is significantly h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 32 publications
3
75
0
Order By: Relevance
“…6b) showed that HOCH 2 OOH appeared at the rst 2 min and slightly decreased aer 5 min, while a gradual increase of HCOOH was shown at the expense of HOCH 2 OOH over time, indicating CH 3 OH can be converted to HOCH 2 OOH and consecutively to HCOOH, in line with previous reports. 17,44 This also agrees well with the tendency of methanol to oxidise, owing to the lower C-H bond strength in methanol (3.88 eV) compared to that of methane (4.50 eV). Notably, as shown in Fig.…”
Section: Resultssupporting
confidence: 82%
“…6b) showed that HOCH 2 OOH appeared at the rst 2 min and slightly decreased aer 5 min, while a gradual increase of HCOOH was shown at the expense of HOCH 2 OOH over time, indicating CH 3 OH can be converted to HOCH 2 OOH and consecutively to HCOOH, in line with previous reports. 17,44 This also agrees well with the tendency of methanol to oxidise, owing to the lower C-H bond strength in methanol (3.88 eV) compared to that of methane (4.50 eV). Notably, as shown in Fig.…”
Section: Resultssupporting
confidence: 82%
“…However, cleaving the first C-H bond in CH 4 is still a great challenge for the high bonding strength in CH 4 molecule. Song and colleagues have decorated isolated chromium atoms on TiO 2 support for direct methane oxidation [ 103 ]. The optimized catalyst exhibits an impressive yield of 57.9 mol/mol Cr and high selectivity (93%) at 50 °C for C 1 oxygenated products.…”
Section: Catalytic Applications Of the Isolated Reactive Centersmentioning
confidence: 99%
“…As the temperature increased, the conversion of NO to NO 2 decreased (Figure S4), as also expected thermodynamically,and this may be one of the reasons for the decrease in DME selectivity with temperature (Table S1). TheD ME productivity was compared to literature values of MeOH, DME, and HCHO productivities from catalytic gas-phase methane partial oxidation with stronger oxidants such as N 2 O, [15,16,[22][23][24] H 2 O 2 , [1] and O 3 [3] at low temperatures ( TheT OF over Pt/Y 2 O 3 compared favorably to results reported with N 2 Oo ver Fe-a nd Cu-based catalysts and was comparable to that using H 2 O 2 over aF eCu/ZSM-5 catalyst. [25] In contrast, the TOFwas substantially lower than that using O 3 over Li/MgO [3] and this was because of substantial contributions from gas-phase reactions in the latter.…”
Section: Resultsmentioning
confidence: 99%
“…Currently methanol is produced by an energy-intensive, two-stage process involving the initial disaggregation of methane to synthesis gas followed by its reassembly,w hile formaldehyde is obtained by the further oxidation of methanol. As ubstantial amount of work has been done on the direct partial oxidation of methane with activated oxidants such as H 2 O 2 , [1] N 2 O, [2] and O 3 [3] and much research has been carried out with the plain oxidant O 2 using oxide catalysts like ferric molybdate, [4] MoO 3 /SiO 2 , [5] and V 2 O 5 /SiO 2 , [6] as covered in recent reviews. [7][8][9][10] Other studies have reported the use of achlorine dioxide radical for the partial oxidation of methane in ap hotocatalytic reaction [11] and the co-conversion of CH 4 and CO 2 to oxygenates over RhVO 3 À cluster anions.…”
Section: Introductionmentioning
confidence: 99%